Employing Smartphone and Compact Camera in Building Measurements - Haval A. Sadeq (Eurasian Journal of Science and Engineering, 2018)
This paper investigates the possibility of implementing images from smartphones and compact cameras for building measurement, such as archaeological buildings, for documentation purposes based on point cloud produced via photogrammetric technique. Images of the object are first captured from different positions. Then, the images are processed for the interior and exterior orientations to produce point cloud. For object registration, one distance is measured at the site, which is assigned to the model and used for scaling. The generated point cloud is subsequently exported into various software, such as AutoCAD for the purpose of taking measurements or for any architectural studies. Two types of smartphone with different camera resolutions and two types of compact camera are used in the test. Results are validated by comparing several real measurements from the site. The quality of the data is proven to be accurate up to centimetre accuracy.